Search for E(5) Symmetry in 102Pd - Ashley, S. F.; et al., ... (HNPS Advances in Nuclear Physics, 2019)
Lifetimes of the excited states in the yrast band of 102Pd have been deter- mined using the Recoil-Distance Doppler Shift experiment at INFN, Labo- ratori Nazionali di Legnaro. Excited states in 102Pd were populated by the 92Zr(13C,3n)102Pd fusion-evaporation reaction. Lifetimes were deduced using the Differential Decay Curve method and the corresponding B(E2) values were compared to the E(5) critical-point symmetry, and also the U(5) and O(6) limits of the Interacting Boson Model-1. It is evident that 102Pd agrees poorly with the predicted E(5) symmetry but has a very good (and somewhat surprising) agreement with the O(6) limit.